2020
DOI: 10.3389/fphar.2019.01688
|View full text |Cite
|
Sign up to set email alerts
|

An Updated Review of Randomized Clinical Trials Testing the Improvement of Cognitive Function of Ginkgo biloba Extract in Healthy People and Alzheimer’s Patients

Abstract: Alzheimer's disease (AD) is a common neurodegenerative disease, mainly manifested by cognitive dysfunction. It seriously reduces the quality of life, and there is no ideal treatment strategy in clinical practice. Clinical studies on the treatment of AD with Ginkgo biloba L. leaf extract (EGb) have been reported since 1980s, and many clinical studies have been carried out during the following 30 years. However, the benefits of EGb on the treatment of AD are still controversial. In this review, we collected the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
51
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 88 publications
(54 citation statements)
references
References 51 publications
1
51
0
2
Order By: Relevance
“…Ginkgolic acid has been studied relatively extensively for its therapeutic effects on cryptosporidiosis [57,58], human immunodeficiency virus (HIV) and HIV infection [59], hypertension [60,61] and cancer [56,62]. Furthermore, G. biloba L. has long been used in traditional Chinese medicine for treating lung and skin diseases [63,64], and its extracts have been assessed also as a remedy for cognitive impairment treatment in people [65,66]. Based on the licenced use of G. biloba extracts [65] and the selective toxicity of ginkgolic acid, it is possible that compound 4 and related compounds from algae, such as S. decipiens, might exert toxic effects selectively towards parasitic cells over mammalian host cells.…”
Section: Discussionmentioning
confidence: 99%
“…Ginkgolic acid has been studied relatively extensively for its therapeutic effects on cryptosporidiosis [57,58], human immunodeficiency virus (HIV) and HIV infection [59], hypertension [60,61] and cancer [56,62]. Furthermore, G. biloba L. has long been used in traditional Chinese medicine for treating lung and skin diseases [63,64], and its extracts have been assessed also as a remedy for cognitive impairment treatment in people [65,66]. Based on the licenced use of G. biloba extracts [65] and the selective toxicity of ginkgolic acid, it is possible that compound 4 and related compounds from algae, such as S. decipiens, might exert toxic effects selectively towards parasitic cells over mammalian host cells.…”
Section: Discussionmentioning
confidence: 99%
“…Even clinical studies have been conducted to assess the effect of Gingko biloba extract in the treatment of Alzheimer’s disease and cognitive function. Extensive analysis has revealed that the consumption of Gingko biloba extract improves the cognitive functioning of individuals who have mild dementia [ 97 ].…”
Section: Plant-based Supplements With Anti-ageing Potentialmentioning
confidence: 99%
“…Befitting their status as flavonoids, they have anti-cancer, anti-microbial, antiviral, and anti-inflammatory properties [16]. In contrast to the extensive studies on drug interaction with flavonoids, data on the inhibitory effects of biflavonoids on P450 and UGT enzymes are rare, though biflavonoids are taken in the form of dietary supplements (e.g., Ginkgo biloba extract [17]). The inhibitory potential of amentoflavone, the major biflavonoid in Cupressus funebris, against P450 and UGT enzymes was only recently reported [18,19].…”
Section: Introductionmentioning
confidence: 99%